Disrupted human–pathogen co-evolution: a model for disease - Kodaman, Nuri; Sobota, Rafal S.; Mera, Robertino; Schneider, Barbara G.; Williams, Scott M. (Frontiers in Genetics, 2014)
A major goal in infectious disease research is to identify the genetic variants—both human and pathogenic—that explain the observed differences in human response to microbial pathogenesis. Neither pathogenic strain nor human genetic variation in isolation has proven adequate to explain the heterogeneity of disease pathology. We suggest that disrupted coevolution between a pathogen and its human hosts can explain variation in disease outcomes, and that genome-by-genome interactions should therefore be incorporated into genetic models of disease caused by infectious agents. Genetic epidemiological studies that fail to take both the pathogen and host into account can lead to false and misleading conclusions about disease etiology. We discuss our model in the context of three pathogens, Helicobacter pylori, Mycobacterium tuberculosis and Human papillomavirus, and generalize the conditions under which it may be applicable.